Antibacterial Effects of Kumquat Peel Essential Oil on Staphylococcus Aureus and Escherichia Coli Bacteria in Comparison With Some Standard Antibiotics - Sara Mosazad; Katayon Agahee; Razzagh Mahmoudi; Shagayegh Moosavi; Saeed Shasavari (The Journal of Qazvin University of Medical Sciences, 2020)
Background Studies have been conducted on citrus fruits and their essential oils in terms of preservative properties and the effect on food safety. Objective This study aimed to examine the antibacterial effects of kumquat peel essential oil. Methods In this experimental study, Kumquat fruit was purchased from the market in Qazvin, Iran. Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of kumquat peel essential oil against Staphylococcus aureus and Escherichia coli strains were measured using broth microdilution method (the range of essential oil concentrations was 25000-12500-6250-3125-1562.5-781.25-390.625-195.31-97.655-48.82 µg/ml), and the diameter of the bacteria growth inhibition zone was determined by diffusion method (the percentage of essential oil was (4×105 µg/ml) and then compared with standard 106-8×105-6×105 -antibiotics. For statistical analysis, independent t-test and one-way ANOVA were used. Findings Their mean levels of MIC and MBC for the essential oil against the Staphylococcus aureus were 0.42±0.18 and 1.04±0.3, and against the Escherichia coli, they were 0.26±0.09 and 0.42±0.18, respectively. Under Disk diffusion, the highest mean diameter of growth inhibition zone for Staphylococcus aureus and Escherichia coli were obtained 12.1 and 10.17 mm, respectively. Conclusion The kumquat peel essential oil has a significant antimicrobial effect on the study bacteria. As an herbal product, it can be useful as an alternative to synthetic drugs and food additives.